Gearing ratio and operating cash flow performance of quoted manufacturing firms in Nigeria - Oranefo, Patricia Chinyere; Egbunike, Chinedu Francis (Goodwood Publishing, 2023)
Purpose: The study examines the effect of gearing ratios on the operating cash flow performance of 36 manufacturing firms listed on the Nigeria Stock Exchange from 2011 to 2018 financial years. The study evaluated the effect of capital gearing, income and the operating gearing ratios on the operating cash flow of quoted manufacturing firms. Research methodology: The study adopts an ex post facto research design utilizing a final sample of thirty-six (36) purposively selected manufacturing firms quoted on the Nigerian Stock Exchange (NSE). The study utilized financial statement data compiled by MachameRATIOS®. The data were analyzed using multiple regression techniques. Results: There is a negative effect of capital and income gearing ratio on operating cash flows with the former not significant, and a positive non-significant effect of operating gearing ratio on operating cash flow. Limitations: The focus on consumer and industrial goods firms limits the generalizability of the study findings to other sectors of the economy. The study did not test for Granger causality. Contribution: The study contributes to the literature in the context of developing countries, on the importance of monitoring the different gearing ratios, more especially the income gearing ratio to ensure positive cash flow. The findings also confirm that managers from emerging economies can alter business risk to sustain favorable performance. The study has implications for investors assessing investment decisions on the need to be wary of the different market and financial risk profiles computed from the various measures in making informed investment decisions.